(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
The article examines the protection and measures for the protection of Leucozonella corona and Archaica eleorica. Leucozonella corona Schileyko et Rymzhanov, 2010 is a weak, naturally rare, locally distributed, endemic species. It is distributed in certain areas in the Chotkal and Kurama m ountain ranges. Archaica eleorika Schileyko et Pazilov, 2003-weak, naturally rare, endemic species. Distributed in the hilly regions of Shahrisabz district, Kashkadarya region.